Foreign direct investment and economic growth in Côte d'Ivoire : An application of the bounds testing approach to cointegration - Bi Goli Jean Jacques Iritié; Jean Baptiste Tiémélé (Cogent Economics & Finance, 2023)
This paper analyzes the contribution of foreign direct investment (FDI) to economic growth in Côte d'Ivoire, for the period 1980-2019. We use the World Development Indicators (World Bank) database. The Autoregressive Distributed Lag (ARDL) cointegration approach results show that, in the short and long-run, FDI negatively impacts economic growth in Côte d'Ivoire. We conjecture that these results are due to the predominance of extractive FDI in Côte d'Ivoire. Indeed, the extractive sector is weakly linked to the national economy and is subject to practices of fraud and corruption. Our results also show the importance of education (human capital) in the country's economic growth. All of these findings suggest the need for selective FDI attraction policies, the integration of the enclave extractive sector into the national economy and the strengthening of the education system for a more efficient human capital capable of absorbing and using new knowledge and high technologies transferred by FDI.
Keywords: C32; F21; O47; O55; 330; ARDL bounds testing; Côte d'ivoire; extractive sector; FDI; economic growth; Toda-Yamamoto causality test